Structural and optical properties of copper oxide thin films prepared by novel “in situ CVD” method - Antoschenko, V.S.; Migunova, A.A.; Frantsev, V.V.; Lavrishchev, O.A.; Nemkayeva, R.R. (Recent Contributions to Physics, 2017)
Thin films of copper oxides were obtained by novel «in situ CVD» method on glass substrates using copper monocloride as precursor. Films were synthesized both in the air atmosphere and in the air-argon atmosphere. The X-ray diffraction patterns showed a change in the phase composition of the films obtained in air during the synthesis. Phase transitions CuO-Cu2O-CuO are characteristic for samples synthesized at 400 °C. A sample of 1 min had a monophasic CuO structure. The first transition from the CuO to Cu2O occurs in the narrow time interval between 1 and 2 minutes of pyrolysis. The second transition from the Cu2O phase to the two-phase form of CuO+Cu2O occured between 3 and 5 minutes of synthesis. On the sample 10 minutes only a small amount of Cu2O was observed. And, finally, a sample synthesized in 20 minutes had a monophasic CuO structure. The phase restructuring is related to the kinetics of the film synthesis process and is determined by the ratio of the rates of supply of copper and oxygen atoms to the interface of the substrate-the growing layer. Films obtained under oxygen deficiency conditions were identified as monophasic Cu2O at the synthesis time of up to 20 minutes. The increase in time led to the formation of mixed phases. The Cu2O films obtained at 500 °C for 1 minute had high transparency with a transmission maximum of 80% at a wavelength of 600 nm. The FWHM values obtained from XRD patterns of the films indicates a high ordering of the crystal structure
Keywords: Copper oxide, XRD, Phase composition, CVD